Cytotoxic and morphological effects of microcystin‐LR, cylindrospermopsin, and their combinations on the human hepatic cell line HepG2. Issue 3 (20th November 2018) - Gutiérrez‐Praena, Daniel; Guzmán‐Guillén, Remedios; Pichardo, Silvia; Moreno, Francisco Javier; Vasconcelos, Vitor; Jos, Ángeles; Cameán, Ana María
Abstract: Cylindrospermopsin (CYN) and Microcystin‐LR (MC‐LR) are toxins produced by different cyanobacterial species, which are found mainly in freshwater reservoirs. Both of them can induce, separately, toxic effects in humans and wildlife. However, little is known about the toxic effects of the combined exposure, which could likely happen, taking into account the concomitant occurrence of the producers. As both cyanotoxins are well known to induce hepatic damage, the human hepatocellular HepG2 cell line was selected for the present study. Thus, the cytotoxicity of both pure cyanotoxins alone (0–5 μg/mL CYN and 0–120 μg/mL MC‐LR) and in combination for 24 and 48 h was assayed, as long as the cytotoxicity of extracts from CYN‐producing and nonproducing cyanobacterial species. The potential interaction of the combination was evaluated by the isobologram or Chou–Talalay's method, which provides a combination index as a quantitative measure of the two cyanotoxins interaction's degree. Moreover, a morphological study of the individual pure toxins and their combinations was also performed. Results showed that CYN was the most toxic pure cyanotoxin, being the mean effective concentrations obtained ≈4 and 90 μg/mL for CYN and MC‐LR, respectively after 24 h. However, the simultaneous exposure showed an antagonistic effect. Morphologically, autophagy, at low concentrations, and apoptosis, at high concentrations were observed, with affectation of the rough endoplasmic reticulum and mitochondria. These effects were more pronounced with the combination. Therefore, it is important to assess the toxicological profile of cyanotoxins combinations in order to perform more realistic risk evaluations.